PENGEMBANGAN BAHAN AJAR E-ENSIKLOPEDIA MEMANFAATKAN APLIKASI CANVA PADA MATA PELAJARAN IPAS MATERI INDONESIAKU KAYA RAYA KELAS V SDN KOTA MALANG: Penelitian Pengembangan - Setiyani, Bela Pramita Indris; Indawati, Ninik; Triwahyudianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teaching materials are all forms of materials used to facilitate teachers in carrying out learning activities in the classroom. Along with the rapid development of technology, innovative learning will create an active, interesting and enjoyable learning atmosphere. This study is the development of interactive E-encyclopedia teaching materials by utilizing the Canva application. The purpose of the study was to determine the development, feasibility and practicality of E-encyclopedia teaching materials utilizing the Canva application in the Science subject of the material My Indonesia is Rich. The subjects in this study were teachers and students of grade V SDN Malang City. This study uses a type of development research or R&D using the ADDIE stage model, namely Analysis, Design, Development, and Implementation. The data collection instruments used were documentation and questionnaires distributed to validators of material experts, media experts, language experts, students and teachers. The results of the study showed that the encyclopedia teaching materials were feasible and very practical to use. The assessment of feasibility by material experts was 79,54%, media experts 86,11% and language experts 100%. Practicality assessment by students was 84,50% and teachers were 88,63%. Based on the presentation of the assessment results, the E-encyclopedia teaching material was declared feasible and very practical to use in learning for fifth grade students at SDN Kota Malang.